The Relationship and Social Interaction Between the Village Head and the Village Consultative Body in Decision-Making for Village Physical Development (Case Study of Tanjungharjo Village, Kapas District, Bojonegoro Regency) - Heriyono, Nowo; Wijaya, Mahendra; Utami, Trisni (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to analyze the roles and interactions of both entities in achieving village development goals. This research employs a qualitative method with a descriptive case study approach, located in Tanjungharjo Village, Kapas District, Bojonegoro Regency. The village was selected due to its contextual relevance for studying the working relationship and social interaction between the village head and the Village Consultative Body (BPD) in physical development decision-making. The research subjects include village members and relevant officials involved in the process. Data collection techniques include in-depth interviews with research subjects, participatory observation during village meetings and development activities, as well as document analysis of various official village records. Data were analyzed inductively and qualitatively, starting with transcription and coding to identify key themes, followed by thematic analysis to explore the dynamics of decision-making. The results of the study indicate that the working relationship between the Village Head and the Village Consultative Body (BPD) in Tanjungharjo Village varies and affects the effectiveness of village development decision-making. A harmonious and mutually supportive relationship creates an inclusive and democratic decision-making environment, while tension or conflict can hinder collaboration. Factors such as differing viewpoints, lack of communication, the dominance of the Village Head, and personal or political conflicts influence this relationship. Enhancing the understanding of the BPD's role, communication, and active participation is necessary to address these challenges. This study aligns with Social Exchange Theory, which emphasizes the importance of positive interaction for decision quality, and supports effective communication, training, and recognition of the BPD's role for successful village development.